PENDEKATAN MULTIKULTURAL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MEMPERKUAT TOLERANSI ANTAR AGAMA - Faizatul Widat; Wiwis Rohmatul Ummah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of a multicultural approach in the learning of Islamic Religious Education (PAI) at SMP Negeri 2 Kraksaan. The main focus of this research is how to prepare materials, deliver materials, classroom interactions, and the role of teachers in instilling the values of tolerance and inclusivity among students. The research method used is a qualitative approach with a case study design, which involves in-depth interviews, observations, and documentation analysis. The results show that the multicultural approach applied has succeeded in creating an inclusive and tolerant atmosphere, even though the majority of students are Muslim. The preparation of materials that prioritize universal values such as compassion, justice, and tolerance, as well as the delivery of material in moderation, plays an important role in forming an open attitude and mutual respect between students. In addition, open classroom interactions and discussions between students from different religious backgrounds also strengthen their understanding of the importance of coexistence in diversity. The role of PAI teachers as agents of change is very significant in instilling these values, both in the classroom and through extracurricular activities that support inclusivity. These findings reinforce evidence from previous research showing that religious education with a multicultural approach can strengthen attitudes of tolerance and appreciation for differences among students.